(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ningrum EW, Patria MP. 2021. Microplastic contamination in Indonesian anchovies from fourteen locations. Biodiversitas 23: 125-134. Microplastics in seawater can enter into the food chain of pelagic fish with subsurface foraging behavior such as anchovies (Stolephorus spp.). Anchovies are valuable commercial fish with high market demand. Hence, measuring potential marine pollutants in these fish is needed. Microplastics as marine contaminants are reportedly more dangerous if they occur together with other contaminants such as trace metals. This research aims to detect microplastic contaminants in anchovies caught in the Indonesia Sea. This research compared between the microplastic contamination on anchovies from 14 harbors: 6 in Western Indonesia (Meulaboh, Krui, Pangkalpinang, Muara Angke, Karimunjawa, and Sidoarjo) and 8 in Eastern Indonesia (Manado, Mamuju, Makassar, Kendari, Ambon, Sorong, Fakfak, and Waingapu). We isolated the digestive tracts of anchovies and measured their length and dry weight. The organic materials were digested with NaOH and a technical-grade sodium Laureth sulfate (SLES) solution approximately one week after collection. Microplastics were observed using a microscope and confirmed with Fourier transform infrared spectroscopy (FTIR). We found that most microplastic contaminants in anchovies were in fiber and film shapes. The majority of the sizes ranged from 50-500 ?m, followed by a range of 20-50 ?m. Microplastics were surprisingly high in samples from Mamuju (688±1.15 MPs idv-1) and Krui (645±7.02 MPs idv-1), higher than any contaminated biota ever reported for anchovies. As reported, anchovies from the Indonesia Sea are contaminated by microplastics. Moreover, human exposure to microplastic contaminants is possible and may affect consumer health in long-term exposure.